Transcriptional activation is a key function encoded by MLL fusion partners - Zeisig, Bernd; Schreiner, Silke; Garcia-Cuellar, Maria-Paz; Slany, Robert (Leukemia, 2003)
Chromosomal translocations that fuse the mixed lineage leukemia gene (MLL) to a variety of unrelated partner genes are frequent in pediatric leukemias. The novel combination of genetic material leads to the production of active oncoproteins that depend on the contributions of both constituents. In a search for a common function amongst the diverse group of MLL fusion partners we constructed artificial fusions joining MLL with generic transactivator and repressor domains (acidic blob, GAL4 transactivator domain, Herpes simplex VP16 activation domain, KRAB repressor domain). Of all constructs tested, only MLL-VP16 was able to transform primary bone marrow cells and to induce a block of early myeloid differentiation like an authentic MLL fusion. Interestingly, the transformation capability of the artificial MLL fusions was correlated with the transcriptional potential of the resulting chimeric protein but it was not related to the strength of the isolated transactivation domain that was joined to MLL. These results prove for the first time that a general biological function - transactivation - might be the common denominator of many MLL fusion partners.
UnivIS-Import:2015-03-09:Pub.2003.med.IB.LPCIPDBI.transc
Keywords: Leukemia; MLL; Transactivator domain; Transcription